A Journey to Excellence: Understanding and Supporting International Graduate and Doctoral Students (Comparative & International Education Series, 2023)
International graduate and doctoral students play a crucial role in the competitiveness of the United States on a global scale, as they are highly represented in STEM programs and provide the US with a valuable supply of highly skilled talent. However, international students face numerous challenges when pursuing higher education overseas, including language barriers, cultural differences, isolation, lack of support networks, and financial constraints. COVID-19 has exacerbated these challenges, with almost 50% of international students reporting financial difficulties due to the pandemic. This chapter reviews how the experiences of international graduate students are shaped by their motivations, support from academic advisors, peer support, and cultural identities. Despite these challenges, international students persist in their programs and bring valuable experiences and perspectives to higher education institutions. To support their success, universities and departmental administrative bodies can consider delivering workshops, building communities for doctoral students, and increasing awareness among university staff and faculties about the needs of a diverse student population.